The Impact of Managerial Accounting Techniques on Short-term Decisions: A Case Study of SMEs in Sulaimani Governorate (Raparin Journal of Humanities (RJH), 2024)
This study aims to determine the importance of managerial accounting in the process of short-term decision-making. Since managerial accounting is a crucial component of the financial information system and is crucial in making decisions in big companies or SMEs, while managerial accounting is only briefly discussed in the majority of economic units, there are some organizations where certified public accountants view managerial accounting as an optional component of the business.Financial data was collected from one of the SME companies in KRG/Sulaimani governorate, which is Mariwan Gallery, located in Bazian. The results indicate that managerial accounting has a significant effect on the process of short-term decision-making. This study recommends that all businesses, including small shops, hire accountants in order to make critical financial decisions. This helps businesses perform better, and it also provides more job opportunities for society.